Pseudo Spiritual Experience Religious and Cultural Tourism in West Java - Rohman, Muhamad Iqbal Budi; Nurrohman, Aif Nanang; Putri, Liska Ananda; Weishaguna, Weishaguna; Kurniasari, Nia (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
This research focuses on the issue of the lack of spiritual experience gained by visitors to religious and cultural tourism in Indonesiatourism cases for the Al Jabbar Grand Mosque, the Mount Padang Site, and the Sagati Cultural Park in West Java.The aim of this research is to identify the spiritual level of visitors to religious and cultural tourism objects in West Java.This problem is solved based on theories of the spiritual experiences of religious and cultural tourism visitors with variablesworship, science, da'wah, tadabur, diversity, self-reflection, and the search for meaning.This research uses two approaches, namely qualitative and quantitative. A qualitative approach was carried out using the Maudhu'i Al Qur'an and Hadith analysis method to identify the main ideas for the development of religious and cultural tourism as a whole.based on visitors' spiritual experiences. The quantitative approach in this research uses a descriptive statistical analysis method of respondents' answers regarding the level of spiritual experience of visitors. The results of this research conclude the classification of the spiritual level of tourist objects through an analysis of the differences between the reality of respondents' satisfaction answers in the field and the theoretical conception of the spiritual experience that visitors should have. This research also provides recommendations for improving the quality of spiritual experiences at religious and cultural tourism objects.